Transforming Arabic for Specific Purposes: Pedagogical Reconstruction for Constitutional Law Students in Islamic Higher Education - Yasmar, Renti; Turkey, Mohamed; Irawan, Bambang (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
Arabic language teaching in many Islamic higher education institutions remains dominated by a general language approach oriented toward everyday communication, while students in non-language disciplines such as law require discipline-specific terminology and academic discourse. This study examines how Arabic instruction can be pedagogically reconstructed to support legal academic literacy among Constitutional Law students. Using a qualitative case study design, the research was conducted in the Constitutional Law Study Program at IAIN Curup, Bengkulu, through classroom observation, interviews, and instructional document analysis. The findings show that the reconstruction occurred in three main aspects: the integration of constitutional and legal terminology into teaching materials, the reframing of sentence contexts from everyday topics to legal-academic issues, and the use of thematic dialogue practice related to legal discourse. This reconstruction led to greater student engagement, stronger awareness of the relevance of Arabic to legal studies, and a shift from general language learning toward discipline-based academic literacy. Unlike much of the existing ASP literature, which often emphasizes linguistic mastery alone, this study highlights Arabic for Specific Purposes as a pedagogical framework for linking language learning with disciplinary knowledge practices in Islamic higher education.